Subluxation and dislocation of the hip in children with spina bifida (review) - A. G. Baindurashvili; S. V. Ivanov; V. M. Kenis (Travmatologiâ i Ortopediâ Rossii, 2013)
Subluxation or dislocation of the hip joint develops in 30-50% children with spina bifida during the first 2-3 years of life. These problems results from force disbalance between muscle group and other structural changes of the hip and pelvis components of the joint. The goal of treatment subluxation and dislocation of the hip joint in children with spina bifida is to make comfortable daily functions, eliminate the pain, provide the mobility and social independent. Management of subluxation and dislocation in children with spina bifida had changed in the last years because of the analysis long-term results. Indications for surgical treatment were determined more clearly, what made the results of treatment better.